Accelerated Short Circuiting in Anode‐Free Solid‐State Batteries Driven by Local Lithium Depletion. Issue 12 (12th February 2023) - Lewis, John A.; Sandoval, Stephanie E.; Liu, Yuhgene; Nelson, Douglas Lars; Yoon, Sun Geun; Wang, Runzi; Zhao, Ying; Tian, Mengkun; Shevchenko, Pavel; Martínez‐Pañeda, Emilio; McDowell, Matthew T.
Abstract: "Anode‐free" solid‐state batteries (SSBs), which have no anode active material, can exhibit extremely high energy density (≈1500 Wh L −1 ). However, there is a lack of understanding of the lithium plating/stripping mechanisms at initially lithium‐free solid‐state electrolyte (SSE) interfaces because excess lithium metal is often used. Here, it is demonstrated that commercially relevant quantities of lithium (>5 mAh cm −2 ) can be reliably plated at moderate current densities (1 mA cm −2 ) using the sulfide SSE Li6 PS5 Cl. Investigations of lithium plating/stripping mechanisms, in conjunction with cryo‐focused ion beam (FIB) imaging, synchrotron tomography, and phase‐field modeling, reveal that the cycling stability of these cells is fundamentally limited by the nonuniform presence of lithium during stripping. Local lithium depletion causes isolated lithium regions toward the end of stripping, decreasing electrochemically active area and resulting in high local current densities and void formation. This accelerates subsequent filament growth and short circuiting compared to lithium‐excess cells. Despite this degradation mode, it is shown that anode‐free cells exhibit comparable Coulombic efficiency to lithium‐excess cells, and improved resistance to short circuiting is achieved by avoiding local lithium depletion through retention of thicker lithium at the interface. These new insights provide a foundation for engineering future high‐energy anode‐free SSBs. Abstract : Anode‐free solid‐state batteries with Li6 PS5 Cl solid electrolytes can support substantial lithium deposition without short circuiting, but they are shown to be fundamentally limited by the non‐uniform presence of lithium during stripping. Characterization and modeling demonstrate that local lithium depletion at the end of stripping decreases the electrochemically active area, leading to current concentration and void formation in anode‐free cells.